Examining gender differences in indigenous chicken commercialisation intent – evidence from North-Western Zambia - Moffat Chawala; Bruce Mwiya; Juvenalis Tembo; Gillian Kabwe (Cogent Business & Management, 2022)
This paper contributes to the smallholder agriculture commercialisation literature by applying the Theory of Planned Behaviour in an under-researched developing country context. The study examines the influence of attitude, subjective norms and perceived behavioural control on the Scaling-Up intent among smallholder village chicken (free-range or indigenous) farmers in North-western Zambia. Additionally, gender differences regarding commercialisation intent are examined. Based on a quantitative correlational design utilising 556 smallholder farmers' primary data from a structured questionnaire, statistical correlation and student's T-test models were employed. The findings indicate that attitudes, subjective norms, perceived behavioural control have unique positive significant effects on commercialisation practices intention (CPI) and CPI in turn positively influences commercialisation scaling-up intention (CSI). Additionally, the study found significant gender differences in all aspects of the model except for subjective norms. Despite the study being cross-sectional and based on one district in Zambia, the findings have important implications. For policymakers and enterprise support institutions, understanding the socio-psychological factors of smallholder farmers is important before introducing any interventions to promote the commercialisation of the village chicken. Additionally, there is a need to encourage farmers to adopt commercialisation practices in livestock management, investment and marketing. This would increase the chances of transitioning from subsistence to commercial farming. In terms of narrowing the gender gap in participation, there is a need for policymakers to tailor interventions that would help improve the attitude of women towards commercialisation and to reduce the perceived barriers. The study pioneers application of the TPB in this context.
Keywords: 650; commercialisation; commercialisation practices Intention; theory of planned behaviour; village/indigenous/free-range chicken